Lymphangioma of the tounge - a case report and review of literature - S. R. Shetty (Nigerian Dental Association, 2009)
Lymphangiomas are uncommon congenital hamartomas of the lymphatic system, usually diagnosed in infancy and early childhood. They are commonly located in head and neck region and rarely present in the oral cavity. Most common site of occurrence in oral cavity is the tongue and it appears as cluster of translucent vesicles resembling the appearance of frog's egg or tapioca pudding. Early recognition is of utmost importance to initiation of proper treatment, and avoiding serious complications. Herewith, we present a case of lymphangioma of tongue with follow up of 3 years.